Spasmolytic effect of Zataria multiflora Boiss leaf extract on rat uterus - MK Gharib Naseri; H Mazlomi; M Goshaiesh; G Vakilzadeh; A Heidari (Institue of Medicinal Plants, ACECR, 2005)
Background: Zataria multiflora Boiss is used in traditional medicine to treat gastrointestinal disorders and menrrhalgia. The inhibitory effect of this herb on rat ileum contractions has also been reported. Objective: The aim of this study was to investigate the effect of Zataria multiflora Boiss hydroalcoholic leaf extract (ZHLE) on isolated rat uterus in the presence of some known uterus stimulants. Method: Pieces of virgin adult rat uterus were mounted in an organ bath containing Tyrode or De Jalon solutions. Uterus contractions were induced by KCl, oxytocin and BaCl2 in presence and absence of ZHLE. Animals in oxytocin studies received an injection of oestradiol valerate (5mg/kg, s.c.) 24 h prior experiment. Results: ZHLE (0.125, 0.25, 0.5, 1 and 2 mg/ml) relaxed the uterus precontracted by KCl (60mM) in a dose-dependent manner (p<0.0001) and at 2mg/ml attenuated the BaCl2 (4mM)-induced uterus contraction significantly (p<0.001). The inhibitory effect of ZLHE on KCl-induced uterus contraction was unaffected by propranolol (1μM). In normal De Jalon solution, ZHLE (0.125, 0.25, 0.5, and 1mg/ml) reduced the oxytocin (10mU/ml)-induced contraction dose-dependently (p<0.0001) but in Ca2+-free De Jalon solution, the stimulatory effect of oxytocin was weaker and also the inhibitory effect of ZHLE was more consistent. In presence of atropine (0.5μM), acetylcholine (0.5μM) failed to induce contraction but KCl (30mM)-evoked contraction and extract diminished the contractile response of KCl. The spasmolytic effect of extract (2mg/ml) on KCl-induced contraction was unaffected by naloxone (1μM). Conclusion: From the obtained results it may be concluded that, the ZHLE may induce its inhibitory effect through blockage of the voltage dependent calcium channels and releasing calcium from intracellular stores in rat uterus smooth muscle. The ineffectiveness of propranolol and naloxone on ZLHE inhibitory effect indicates that adrenergic and opoids agonist substance(s) did not exist in the extract. It seems that there was no anticholinergic substance(s) in the extract. The results support the usage of this plant in traditional medicine.